Researchers Productivity Level Clustering Based On H-Index and Citation Using The Fuzzy C-Means Algorithm - Mira Orisa; Ahmad Faisol (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
The fuzzy C-Means algorithm is a partition-based clustering algorithm.Fuzzy C-Means is very helpful in modeling data whose distribution has outliers. Outliers are where there is a data object that is far apart from the existing clusters. Fuzzy C-Means groups data by minimizing the membership function of a data set. so that each piece of data can be a member of more than one group. In this study, the dataset used was the paper citation vs. H-index dataset in the Kaggle.com repository. This dataset is known to have outliers in fuzzy C-Means and has better performance compared to the K-Means and K-Medoid algorithms in modeling datasets that have outliers.